Mediation in criminal proceedings: legal regulation in Ukraine and foreign experience of application - Oleksandr, Motliakh; Vadym, Bezusyi; Oleksandr, Chudnovskyi; Serhii, Burlakov; Hennadii, Shevchuk (Cuestiones Políticas, 2020)
The purpose of the article is to study those conceived of the use of the mediation institution in the criminal proceedings of European countries to implement positive experience in Ukrainian law. The theme of the study is the institution of mediation in criminal proceedings. The following scientific methods were used in the research: dialectical, formal and logical, and legal, system and functional, comparative and legal, legal and other modeled methods. We study the concetorities of the regulation and legal of mediation in criminal proceedings in Ukraine, as well as the practice of its implementation, which is more than modest with other European states. Therefore, we draw on the experience of countries such as Germany, Poland, and the United Kingdom. It is concluded that, given the successful functioning of the mediation institution in most countries, we propose to emulate this positive practice and a separate law "On Mediation" in Ukraine. It is established that the main right for the legislative registration of mediation in Ukraine is the lack of information on the existence of such a way of resolving a criminal case.